Obraz świata w mikrotoponimii Pomorza Gdańskiego - Szuta, Jarosław (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
This section is the first part of a project to recreate the world, which was seen through the eyes of people making up the names of places no inhabited.